The role of physical activity in type 1 diabetes: a review of the literature - Gaszyńska, Monika; Drzewiecka, Antonina; Drzewiecki, Artur; Korczak, Wiktor; Madejska, Maria Anna; Rudzka, Aleksandra; Falkowski, Wojciech; Krysińska, Anna; Woźniak, Weronika; Magielski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Diabetes is a prevalent metabolic disorder affecting over 530 million people globally, with its incidence increasing alarmingly. Due to the early onset of type 1 diabetes (T1D), treatment and prevention of complications are critical. This study aims to present the safety profile of physical activity, its effects on metabolic processes, and the benefits of exercise in preventing late complications of T1D. Review methods: Data were collected using databases such as PubMed and Google Scholar. Over 30 studies and scientific publications published in English or Polish were analyzed, considering keywords such as “type 1 diabetes”,“physical activity”, “exercise”, “aerobic exercise”, “anaerobic exercise”. State of Knowledge: Depending on the type of exercise performed, the body of a diabetic behaves somewhat differently. There is a risk of hypoglycemia during or after aerobic exercise, although some studies have not confirmed such a relationship. Systematic aerobic activity has been proven to benefit carbohydrate metabolism, lipid metabolism, blood vessels and overall body condition. Anaerobic exercise may temporarily raise blood glucose levels and introduce additional stress factors. However, combining both types of exercise can effectively stabilize glycemic levels and improve quality of life. Additionally, exercise has been shown to mitigate long-term diabetes complications. Conclusion: Historically, diabetes was viewed as a disease that restricted physical activity. However, current evidence supports the recommendation of physical exercise for T1D patients. Proper education, treatment advancements, and self-monitoring allow even high-intensity activities to be safely performed.